2002
DOI: 10.1097/00005392-200212000-00032
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study Comparing Paroxetine Alone Versus Paroxetine Plus Sildenafil in Patients With Premature Ejaculation

Abstract: Paroxetine combined with sildenafil appears to provide significantly better results in terms of ejaculatory latency time and intercourse satisfaction versus paroxetine alone in potent patients with premature ejaculation. However, combined treatment is associated with a mild increase in drug related side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(135 citation statements)
references
References 21 publications
5
126
1
3
Order By: Relevance
“…Between 1973 and 2003, there have been 35 studies 15,17,23-25,60-79,80,81 on daily treatment with clomipramine, a tricyclic antidepressant, and on SSRIs (Table 2). In the same period, on-demand antidepressant treatment results were reported in eight studies [82][83][84][85][86][87][88][89] (Table 3). The current review consists of 3034 males obtained from 79 studies.…”
Section: General Results Of Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 1973 and 2003, there have been 35 studies 15,17,23-25,60-79,80,81 on daily treatment with clomipramine, a tricyclic antidepressant, and on SSRIs (Table 2). In the same period, on-demand antidepressant treatment results were reported in eight studies [82][83][84][85][86][87][88][89] (Table 3). The current review consists of 3034 males obtained from 79 studies.…”
Section: General Results Of Reviewmentioning
confidence: 99%
“…[33][34][35]67,76,85 Baseline periods ranged from 1 68,69 or 2 26,27 to mostly 4 weeks. 49,57,65,[77][78][79][80]89 In some studies, a certain number of intercourses 41,60,74,81 was taken as baseline measurement.…”
Section: Baseline Periodmentioning
confidence: 99%
“…IELT was prolonged in patients, who were taking sildenafil, but the difference was not statistically significant; this was probably because of the incorrect definition of PE used (IELT p2 min in 75% of intercourse attempts during the run-in period) or because of the fact that no treatment effect was found regardless of the criteria used to define PE. Salonia et al 17 showed improvements in stopwatch-measured IELT, sexual satisfaction and frequency of intercourse with sildenafil plus paroxetine over paroxetine alone in men with IELT o1 min. In a prospective randomized clinical trial, Wang et al 18 showed that sildenafil was superior to paroxetine and squeeze technique in improving IELT in men with PE and without ED.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the SV might be the most important target organ for the monitoring of ejaculatory responses. [4][5][6][7] Previous isolated rat SV studies have investigated the effects of drugs or electrical field stimulation (EFS) on the SV smooth muscle; generally, these studies have used the strip tissue preparation after removing the surrounding connective and fat tissues. Once the tissues were appropriately prepared, the isometric contractions of the suspended strip in the organ chamber were recorded.…”
Section: Introductionmentioning
confidence: 99%